KEMAMPUAN MEMBACA NYARING SISWA SDI BEA KAKOR, KECAMATAN RUTENG - Fransiska Jaiman Madu; Margareta Saiman Jaman (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
Reading aloud a passage is certainly not easy, reading aloud or reading aloud is not an activity as long as it sounds the written symbol, but the reader must master the elements of reading aloud that must be applied when the reading activity takes place. If this is not done, then the sentence or reading that is read will lose its meaning. The elements of reading aloud are intonation, pronunciation, pause, tempo, pause, stress, and volume. These elements must be mastered by the reader. However, this is not the case at SDI Bea kakor. Fourth grade elementary school children have low aloud reading ability. The children make the sound when reading without paying attention to the techniques and elements as mentioned earlier. As a result, the children do not even understand the contents of what they read. The problem certainly has a causal factor. After the research was conducted, it turned out that there were so many factors that caused the low ability of students to read aloud. These factors include children's physical factors, gender differences, children's intellectual/intelligence factors, lack of student understanding of the content of reading, methods used by teachers who are less innovative, students' family environment, children's motivation and interests, and children's self-confidence. Furthermore, several solutions were offered to overcome the problems faced by children at SDI Bea Kakor, namely; 1) the use of repetitive exercise methods and; 2) the formation of the habit of reading aloud in children, which aims for children to have a culture of reading aloud.